Health and Economic Outcomes Among the Alumni of the Wounded Warrior Project 2013 - Cerully, Jennifer L. (RAND Corporation, 2014)
In this report, the authors use the Wounded Warrior Project's 2013 survey of its members (alumni) to understand the physical, mental, and economic challenges that Wounded Warriors face. The researchers find that at least half of alumni reported dealing with mental health conditions such as depression and posttraumatic stress disorder, and many of these alumni reported difficulties or delays in seeking mental health care, or not doing so at all.